The Onomastic Universe in the Fantastic Prose of Mikhail Bulgakov: the Dimension of Translation - Inga DRUȚĂ (Philologia, 2022)
Proper names are double-character words: national and international. This is why translation requires an in-depth knowledge of the culture and civilization of the source language people. If a name is used for communication purposes (in a literary work), it must be treated in a special way. These are the most difficult cases for a translator, who has to be creative. Transferring names from one culture to another requires communication skills, but also intercultural skills: respect for traditions and cultural values. Proper names-anthroponyms can only be translated in certain contexts, where they describe a character, but are usually preserved intact. Usually proper names from stories, nicknames, but also some suggestive literary character names are translated and adapted. In most cases, the names of literary characters are not translated, but reported over to facilitate cultural transfer and eventually annotated. Thus, the translation process oscillates between science and art.